Immunoglobulin E‐Mediated Hypersensitivity Reaction to Ketamine. Issue 7 (23rd June 2016) - Ozcan, John; Nicholls, Katherine; Jones, Karin
Abstract: Introduction: Ketamine is a commonly used analgesic agent in the management of both acute and chronic pain. While dose‐dependent side effects are well described, allergy to ketamine is extremely rare. Case: A 41‐year‐old woman with chronic pelvic pain and previous ketamine exposure developed a widespread urticarial rash and mild perioral edema following the initiation of a ketamine infusion. The infusion was ceased and the patient was treated with oral antihistamine, with rapid resolution of symptoms. Serum tryptase levels were elevated at 2 and 6 hours after the infusion was ceased, and subsequent intradermal skin testing supported the diagnosis of type I hypersensitivity reaction to ketamine. Discussion: This case represents a likely immunoglobulin E‐mediated type I hypersensitivity reaction to ketamine, supported by elevated tryptase levels and positive intradermal skin testing. The interpretation of these results and likely mechanism of the hypersensitivity reaction are described. The patient and treating team were advised against subsequent use of ketamine, due to the risk of serious adverse systemic reaction with repeat exposure.